Multisystem failure and death due to extensive hemorrhaging and brain herniation subsequent to a bite by an unidentified snake. Issue 1 (December 2016) - Ehelepola, N.; Samaranayake, S.; Basnayake, B.; Amiyangoda, C.; Dhanapala, D.; Kalupahana, K.
Abstract Background Snakebites cause considerable morbidity and mortality in tropical and subtropical countries even though existing treatment methods can prevent most deaths if presentation occurs early to hospitals. Envenomation by unidentified snakes is common in central Sri Lanka. Management of such patients is challenging especially if presentation is late. Case presentation Here, we report a case of a 52-year-old man from central Sri Lanka who presented late after being bitten by an unidentified snake. He developed `severe coagulopathy, neurotoxicity, acute kidney injury, and rhabdomyolysis. Subsequently, despite of treatment, he died due to extensive hemorrhaging in many organs. A large intracranial hemorrhage lead to fatal brain herniation. Conclusions Envenomation by some snake species can severely affect multiple body systems and give rise to fatal brain hemorrhages and brain herniation. Considering the known effects of local snake venom, the responsible species is likely to be Russell's viper (Daboia russelii ). We recommend some simple measures to reduce the chances of such deaths in the future.